2005
DOI: 10.1086/430912
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aminoglycoside and β‐Lactam Combination Therapy versus β‐Lactam Monotherapy on the Emergence of Antimicrobial Resistance: A Meta‐analysis of Randomized, Controlled Trials

Abstract: Compared with beta-lactam monotherapy, the aminoglycoside/ beta-lactam combination was not associated with a beneficial effect on the development of antimicrobial resistance among initially antimicrobial-susceptible isolates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
96
0
7

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 198 publications
(105 citation statements)
references
References 69 publications
2
96
0
7
Order By: Relevance
“…Evidence derived from clinical and in vitro studies reveals that a combination of antibiotics might prevent the emergence of resistant strains during therapy (39,40). However, clinical data do not clearly support the idea that antibiotic combinations reduce the emergence of resistance (41). Synergy is another potential benefit arising from the use of antibiotic combinations (42)(43)(44), but in vitro synergy of specific antibiotics may not always translate into clinical effectiveness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence derived from clinical and in vitro studies reveals that a combination of antibiotics might prevent the emergence of resistant strains during therapy (39,40). However, clinical data do not clearly support the idea that antibiotic combinations reduce the emergence of resistance (41). Synergy is another potential benefit arising from the use of antibiotic combinations (42)(43)(44), but in vitro synergy of specific antibiotics may not always translate into clinical effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is clinical evidence suggesting that the tigecycline-colistin combination may be superior to colistin monotherapy in terms of emergence of colistin resistance during therapy for infection due to carbapenem-resistant K. pneumoniae (39). In contrast, a meta-analysis focusing on beta-lactams showed that a beta-lactam combined with an aminoglycoside was not superior to beta-lactam monotherapy with regard to emergence of resistance (41). Administration of colistin in combination with an aminoglycoside has also been reported (11,14,16,25); however, attention should be paid during therapy since both agents can cause nephrotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of 8 randomized, controlled trials comparing ␤-lactam monotherapy with ␤-lactam and aminoglycoside combination therapy was conducted, with the primary outcome of emergence of resistance and a secondary outcome of the development of a superinfection (23). Antimicrobial-resistant organisms were defined as bacterial isolates that became resistant to the administered drug during therapy with a change from "susceptible" to "intermediate" or "resistant" or from "intermediate" to "resistant."…”
Section: Prevention Of Resistancementioning
confidence: 99%
“…Such interactions between drugs are classified as additive, synergistic, or antagonistic depending on whether their combined effect on bacterial growth is equal to, greater than, or less than expected based on the inhibitory abilities of the individual drugs (8,9). Two main goals of drug treatment are stopping bacterial growth and preventing the evolution of drug resistance (5,(10)(11)(12). Although synergistically interacting drugs are often favored because of their greater combined ability to inhibit growth (13), little direct evidence for their ability to suppress the evolution of resistance exists, and some studies even suggest the contrary (14)(15)(16)(17)(18).…”
mentioning
confidence: 99%